Avaliação da eficácia da membrana de quitosana impregnada ou não com ciprofloxacino na profilaxia da osteomielite em fraturas expostas: estudo experimental em ratos - Lincoln Paiva Costa (2014)
Introduction: The incidence of open fractures is increasing and even with the use of treatment protocols, the osteomyelitis rate is high. One of the steps of its treatment is systemic antimicrobial prophylaxis. Topical application of antimicrobials is an alternative providing high concentration of antimicrobial at the fracture, low systemic concentration and less side effects. The most widely used vehicle for this purpose is the polymethylmethacrylate, which has its use restricted to thermostable drugs and with powder formulation, additionally it is not biodegradable. Chitosan is biodegradable, antibacterial, and allows the storage and distribution of antibiotics, being an alternative to polymethylmethacrylate. Objective: evaluate the efficacy of prophylaxis of osteomyelitis at models of open fractures using chitosan film with ciprofloxacin or pure. Materials and Method: 24 Holtzman rats were used divided into 4 groups. CT group: model of open fracture treated with systemic antimicrobial, IC group: model of open fracture without treatment, Q group: model of open fracture treated by chitosan film, QA group: model of open fracture treated by chitosan film with antimicrobial. After 3 weeks, the animals were underwent euthanasia through overdose of anesthetics and the left rear femur was removed to histological and microbiological analysis. The histological classification used Smeltzer system and microbiological analysis used qualitative culture. Comparisons between groups were carried out considering significant p values 0,05. Results: The results of animals culture from CT group were less positive when compared with the results of the cultures of the CI group (p = 0.005), Q group (p = 0.005) and QA group (p = 0.009). Evaluating degree of bone inflammation through Smeltzer system showed significant difference in the total score of the CT group animals in comparison to animals from the CI group (p = 0.014) Q group (p = 0.001) and QA group (p = 0.007). Conclusion: In this experimental model of open fracture pure chitosan film or chitosan film with ciprofloxacin were not effective for preventing osteomyelitis.